Attention fluctuations impact ongoing maintenance of information in working memory - Hakim, Nicole (Psychon Bull Rev, 2020)
Working memory maintains information in a readily accessible state and has been shown to degrade as the length of the retention interval increases. Previous research has suggested that this decline is attributable to changes in precision as well as sudden loss of item representations. Here, by measuring trial-to-trial variations in performance, we examined an orthogonal distinction between the maximum number of items that an individual can store, and the probability of achieving that maximum. Across two experiments, we replicated the finding that performance declines after long (10 second) retention intervals, as well as past observations that forgetting was due to probabilistic dropping of individual items rather than all-or-none losses of the stored memories. Critically, longer retention intervals did not reduce the maximum amount of information that could be stored in working memory. Instead, lower attentional control accounted for a decreased probability of maintaining the maximum number of items in working memory. Thus, longer retention intervals impact working memory storage via fluctuations in attentional control that lower the probability of achieving a stable maximum storage capacity.